2023
DOI: 10.2147/jir.s421196
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immuno-Inflammation-Related Biomarkers for Acute Myocardial Infarction Based on Bioinformatics

Hongjun You,
Mengya Dong

Abstract: Previous studies have confirmed that inflammation and immunity are involved in the pathogenesis of acute myocardial infarction (AMI). However, only few related genes are identified as biomarkers for the diagnosis and treatment of AMI. Patients and Methods: GSE48060 and GSE60993 datasets were retrieved from Gene Expression Omnibus. The differentially expressed immuno-inflammation-related genes (DEIIRGs) were obtained from GSE48060, and the biomarkers for AMI were screened and validated using the "Neuralnet" pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 98 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…Our initial observations reveal that overexpression of CBLB significantly curtailed the degree of myocardial infarction in AMI mice, which is consistent with our hypothesis. This observation aligns with the research by Hongjun You et al [ 9 ], which identifies CBLB as an essential immune-inflammation-related biomarker of AMI, reporting a significant decrease in CBLB levels in AMI patients. Both findings mutually reinforce the role of CBLB in AMI, underscoring its significance.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our initial observations reveal that overexpression of CBLB significantly curtailed the degree of myocardial infarction in AMI mice, which is consistent with our hypothesis. This observation aligns with the research by Hongjun You et al [ 9 ], which identifies CBLB as an essential immune-inflammation-related biomarker of AMI, reporting a significant decrease in CBLB levels in AMI patients. Both findings mutually reinforce the role of CBLB in AMI, underscoring its significance.…”
Section: Discussionsupporting
confidence: 92%
“…Research has suggested that Cbl-b may serve as a potential biomarker for AMI, which provides evidence that Cbl-b expression is significantly downregulated in AMI patients compared to the control group, as demonstrated by both public database analysis and analysis of 20 peripheral blood samples [ 9 ]. These findings further underscore the potential role of Cbl-b in the pathogenesis and progression of AMI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LASSO algorithm, a regression analysis model capable of feature selection, has been used to identify biomarkers for various diseases. 24 , 25 The LASSO regression algorithm was implemented using the glmnet package in R software to identify candidate diagnostic biomarkers for distinguishing HCM and control samples. SVM-RFE is a supervised machine learning algorithm that combines a support vector machine approach with recursive feature elimination.…”
Section: Methodsmentioning
confidence: 99%
“…They observed that inflammation-related genes such as NR4A2 , IRAK3 , NFIL3 , IL1R2 , CLEC4E and BCL3AMI were highly up-regulated, indicating that inflammation is an important feature of MI. Another study employed a bioinformatic analysis to pinpoint eight key immuno-inflammation-related genes, namely SH2D1B , ADM , PI3 , MMP9 , NRG1 , CBLB , RORA , and FASLG , which have been identified as potential biomarkers for AMI ( 100 ). Zhuo et al ( 101 ) constructed an MI-related lncRNA-miRNA-mRNA network using RNA sequencing data and identified lncRNA SNHG8, hsa-miR-411-5p, SOCS3 and ICAM1 were key nodes in the network.…”
Section: Single-omics Approachesmentioning
confidence: 99%